2005
DOI: 10.1002/ejic.200400952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anthracene and Pyrene Units on the Interactions of Novel Polypyridylruthenium(II) Mixed‐Ligand Complexes with DNA

Abstract: 2‐(9‐Anthryl)‐1H‐imidazo[4,5‐f][1,10]phenanthroline (aip) and [2‐(1‐pyrenyl)‐1H‐imidazo[4,5‐f][1,10]phenanthroline (pyip) and their complexes [Ru(phen)2(aip)]2+ (1) and [Ru(phen)2(pyip)]2+ (2) (phen = 1,10‐phenanthroline) have been synthesized and characterized by elemental analysis, UV/Vis, IR and 1H NMR spectroscopy, FAB‐MS and cyclic voltammetry methods. Both 1 and 2 are redox‐active and undergo oxidation at 1.43 and 1.47 V (vs. SCE), respectively. Both 1 and 2 show only the 3MLCT emission typical of any po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 58 publications
5
67
0
Order By: Relevance
“…hydroxy, carboxyl and amino groups may respond sensitively to the changes in environmental pH, providing a chance to make pH sensing or switching molecular devices, [3] and to greatly modulate their biological functionalities. [4] The ruthenium(ii) complexes containing imidazole groups have been well studied with respect to their interaction with DNA [5][6][7][8] or reversible acid-base interconver-ground-and excited-state ionization constants were derived. The results indicated that the complex intercalatively bound to the DNA, with an intrinsic binding constant of (8. sion.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxy, carboxyl and amino groups may respond sensitively to the changes in environmental pH, providing a chance to make pH sensing or switching molecular devices, [3] and to greatly modulate their biological functionalities. [4] The ruthenium(ii) complexes containing imidazole groups have been well studied with respect to their interaction with DNA [5][6][7][8] or reversible acid-base interconver-ground-and excited-state ionization constants were derived. The results indicated that the complex intercalatively bound to the DNA, with an intrinsic binding constant of (8. sion.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen atoms were located by difference synthesis and refined isotropically. The final conventional R indices were R(F) = 0.0601 and wR(F 2 ) = 0.1496 for 2391 reflections I Ͼ 2σ(I) with weighting scheme, w = 1/[σ 2 (F o 2 ) + (0.0905P) 2 ], where P = (F o 2 + 2F c 2 )/3. The molecular graphics were plotted using SHELXTL.…”
Section: Methodsmentioning
confidence: 99%
“…This is similar to the DNA cleavage mediated by the Fe-bleomycin complex and its mimetic compounds. [23] Additionally, Xu et al [24] have investigated the interaction of DNA with a diiron complex Fe 2 (DTPB)(µ-O)(µ-Ac)-Cl(BF 4 ) 2 [DTPB = 1,1,4,7,7-penta(2Ј-benzimidazol-2-ylmethyl)triazaheptane, Ac = acetate] by spectroscopic methods. In addition, the hydrolytic cleavage of the supercoiled and linear DNA by the diiron complex was supported by evidence from anaerobic reactions, free-radical quenching, high-performance liquid chromatography experiments, enzymatic manipulation, footprinting analysis, and so forth.…”
Section: Nnnјnјј-tetrakis(2-benzimidazolylmethyl)-2-hydroxy-13-dimentioning
confidence: 99%
See 1 more Smart Citation
“…They constitute versatile components of metallomesogens or behave as mesogenic phase without metal component in the design of liquid crystals [13][14][15][16]. In addition, they play key roles in spectroscopic biosensing of nucleic acids owing to site-selective and adaptive binding to DNA in intercalative mode and in the development of unique chemotherapeutics where they impact on the functions of DNA within cancerous cells [17][18][19][20][21][22][23][24][25][26][27]. Therefore, imp derivatives seem to attract much more interest with many attempts to synthesize and design new materials with the above-mentioned properties.…”
Section: Introductionmentioning
confidence: 99%